Tyrosine Hydroxylase and DOPA Decarboxylase Are Associated With Pupal Melanization During Larval–Pupal Transformation in Antheraea pernyi - Wang, Qi; Zhong, Liang; Wang, Yong; Zheng, Shengwei; Bian, Yumeng; Du, Junhao; Yang, Ruisheng; Liu, Wei; Qin, Li (Frontiers in Physiology, 2022)
In insects, melanism plays important roles in defense, immunoreactions, and body color. The underlying molecular mechanisms of melanism in different insects are diverse and remain elusive. In contrast to another silkworm, Bombyx mori, the Chinese oak silkworm, Antheraea pernyi, produces melanic pupae under natural environmental conditions. DOPA and dopamine synthesis are crucial for melanin formation. Disruption of these processes reportedly influences body colors in many insects. Most research focuses on newly-emerged pupae, and the larval process preceding pupation remains unknown. Due to the large size and long pupation period in A. pernyi, the entire process was studied at least every 12 h. The expression patterns of tyrosine hydroxylase (TH) and DOPA decarboxylase (DDC), which are involved in DOPA and dopamine synthesis in the epidermis, were evaluated during larval–pupal metamorphosis. We also performed RNA interference (RNAi) and used enzyme inhibitors to examine morphological changes. The amino acid sequences of TH and DDC share 90.91% and 86.64% identity with those of B. mori. TH and DDC expression was upregulated during the 48–72 h period prior to pupal emergence, especially at 60 h. RNAi of TH and DDC induced partial melanism in some pupae. The inhibitors 3-iodo-tyrosine (3-IT) and L-α-methyl-DOPA (L-DOPA) influenced pupal melanization. Different concentrations of inhibitors led to pupal deformity and even mortality. Four different monoamines, only DOPA and Dopamine synthezed from Tyrosine will be influenced by TH and DDC inhibitor. These results indicate that TH and DDC are key genes associated with pupal melanization during larval–pupal transformation in A. pernyi. Overall, our results suggest that TH and DDC expression alterations in a particular stage can affect body color, setting the molecular basis for artificial control of pupal melanization.